Developing ACASI questionnaires in Borno State, Nigeria during COVID-19: Using data-informed processes to address complexity, sensitivity, and functionality of family functioning and wellbeing measures. Issue 12 (2nd December 2022) - Seff, Ilana; Steven, Shadrack; Deitch, Julianne; Akika, Veronica; Puls, Cassondra; Okoro, Charles; Sughrue, Scott; Stark, Lindsay
ABSTRACT: Audio Computer-Assisted Self-Interview (ACASI) has become increasingly popular for collecting data on sensitive topics among populations with lower levels of literacy. However, the development of an ACASI tool is an involved process that can be further complicated when working in humanitarian contexts during the COVID-19 pandemic. This study describes the development of an ACASI tool to be used in a family-focused intervention evaluation. Participants included adolescent girls aged 10-14, adolescent boys aged 15-19, and caregivers in Borno State, Nigeria.  Data to inform the tool's development were collected using cognitive interviews, ACASI demonstrations, and post-demonstration assessments with adolescent girls, adolescent boys, and caregivers, as well as a focus group discussion with enumerators. Data found high levels of acceptance for the tool and helped identify appropriate visual representations for various answer options to maximize usability. The survey was found to be too long to administer solely through ACASI; the final tool employs a combination of ACASI and computer-assisted personal interview formats. Findings highlight the importance of repeatedly piloting and testing these types of tools to ensure content and language resonate with intended users. However, the steps employed demonstrate that researchers can maintain a commitment to developing high-quality, community-grounded research tools despite challenges germane to humanitarian settings.